2019
DOI: 10.1002/1873-3468.13329
|View full text |Cite
|
Sign up to set email alerts
|

Crystal structure of the human Scribble PDZ1 domain bound to the PDZ‐binding motif of APC

Abstract: Scribble (SCRIB) is an important adaptor protein that controls the establishment and maintenance of apico‐basal cell polarity. To better understand how SCRIB controls cell polarity signalling via its PDZ domains, we investigated human SCRIB interactions with adenomatous polyposis coli (APC). We show that SCRIB PDZ1, PDZ2 and PDZ3 are the major interactors with the APC PDZ‐binding motif (PBM), whereas SCRIB PDZ4 does not show detectable binding to APC. We then determined the crystal structure of SCRIB PDZ1 doma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
17
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 45 publications
3
17
0
Order By: Relevance
“…The overall mode of Vangl2 peptide engagement is conserved across all three PDZ domain complexes, with PDZ1, PDZ2 and PDZ3 engaging Vangl2 in a manner where the peptide is bound in an anti-parallel orientation compared to the second β-strand whilst being sandwiched by the α2 helix in the canonical binding pocket of the PDZ domains. A comparison of the PDZ1 and PDZ3 domain structures on their own with their Vangl2 complex counterparts revealed no significant movement of secondary structure elements upon Vangl2 binding, as previously observed in complexes of PDZ1 and PDZ3 with -PIX (Lim et al, 2017) and PDZ1 complexes with APC (How et al, 2019) and MCC (Caria et al, 2019 (Figure 2 B), key features of the PDZ1:Vangl2 complex are conserved, with V521 Vangl2 being located in a pocket formed by L872 PDZ2 , F874 PDZ2 , I876 PDZ2 , V932 PDZ2 and L935 PDZ2 , whilst the C-terminal carboxyl group forms hydrogen bonds with the main chain of L872 PDZ2 , G873 PDZ2 and F874 PDZ2 . Additional interactions are formed by S520 Vangl2 :S875 PDZ2 , T519 Vangl2 :H928 PDZ2 , as well as a salt bridge between E518 Vangl2 :S895 PDZ2 .…”
Section: Crystal Structures Of Pdz2:vangl2 and Pdz3-vangl2 Complexessupporting
confidence: 77%
See 3 more Smart Citations
“…The overall mode of Vangl2 peptide engagement is conserved across all three PDZ domain complexes, with PDZ1, PDZ2 and PDZ3 engaging Vangl2 in a manner where the peptide is bound in an anti-parallel orientation compared to the second β-strand whilst being sandwiched by the α2 helix in the canonical binding pocket of the PDZ domains. A comparison of the PDZ1 and PDZ3 domain structures on their own with their Vangl2 complex counterparts revealed no significant movement of secondary structure elements upon Vangl2 binding, as previously observed in complexes of PDZ1 and PDZ3 with -PIX (Lim et al, 2017) and PDZ1 complexes with APC (How et al, 2019) and MCC (Caria et al, 2019 (Figure 2 B), key features of the PDZ1:Vangl2 complex are conserved, with V521 Vangl2 being located in a pocket formed by L872 PDZ2 , F874 PDZ2 , I876 PDZ2 , V932 PDZ2 and L935 PDZ2 , whilst the C-terminal carboxyl group forms hydrogen bonds with the main chain of L872 PDZ2 , G873 PDZ2 and F874 PDZ2 . Additional interactions are formed by S520 Vangl2 :S875 PDZ2 , T519 Vangl2 :H928 PDZ2 , as well as a salt bridge between E518 Vangl2 :S895 PDZ2 .…”
Section: Crystal Structures Of Pdz2:vangl2 and Pdz3-vangl2 Complexessupporting
confidence: 77%
“…ITC measurements revealed that PDZ1E814G and PDZ3P1043L lost binding to both -Pix and APC in addition to Vangl2. In contrast, PDZ1Q808H and PDZ3R1044Q bound interactors with affinities comparable to wild-type PDZ (Lim et al, 2017) and APC (How et al, 2019), with PDZ1Q808H binding -Pix with 10.4 M, APC with 6.0 M and Vangl2 with 10.4 M, whereas PDZ3R1044Q bound -Pix with 14.1 M, APC with 27.4 M and Vangl2 with 20.9 M. PDZ1H793A showed only a significant decrease in binding to -Pix (62.77 M),…”
Section: Crystal Structures Of Pdz2:vangl2 and Pdz3-vangl2 Complexesmentioning
confidence: 88%
See 2 more Smart Citations
“…Work from several labs has shown that Scribble directly interacts through its PDZ domains with proteins playing a role in different steps of cancer development and dissemination. Direct interactions have been reported with tumor suppressors mutated in cancer, Adenomatous polyposis coli (APC), a major component of Wnt signaling [39], the lipid phosphatase PTEN [40], MCC (Mutated Colorectal Cancer) [41], and with ZO-2, a junctional protein downregulated during cancer progression [42]. The Scribble PDZ domains also tightly bind to the PDZBM of the Guanine Exchange Factor (GEF) β-PIX/ARHGEF7 which promotes cancer cell migration [43,44].…”
Section: Pdz Interactionsmentioning
confidence: 99%